Empirical Bayes Credibility Models for Economic Catastrophic Losses by Regions - Jindrová, Pavla; Kopecká, Lucie (EDP Sciences, 2016)
Catastrophic events affect various regions of the world with increasing frequency and intensity. The number of catastrophic events and the amount of economic losses is varying in different regions of the world. Part of these losses is covered by insurance. Catastrophe events in last years are associated with increases in premiums for some lines of business. The article focus on estimating the amount of net premiums that would be needed to cover the total or insured catastrophic losses in different regions of the world using empirical credibility models.
Empirické Bayesovské kredibilní modely pro regionální ekonomické katastrofické škody
Keywords: Catastrophic events; economic losses; regions of the world; empirical credibility models.; Katastrofické události; ekonomické škody; světové regiony; empirické kredibilní modely.